ANALYSIS OF PORK DEMAND IN RUTENG CITY TRADITIONAL MARKET, MANGGARAI REGENCY, EAST NUSA TENGGARA PROVINCE - H. D, TUKAN; DALLE, N. S.; NUGRAHA, E. Y.; ADVENTTEN, G. G. F.; GONAL, P. S.; SEKAR, V. K. (Majalah Ilmiah Peternakan; Vol 28 No 1 (2025): Vol. 28 No. 1 (2025)DO - 10.24843/MIP.2025.V28.i01.p06, 2025)
This study aims to determine the influence between pork price variables, prices of other goods and consumer tastes on the number of pork demand in the traditional market. This research has been conducted from January to March 2024 on 49 respondents in the traditional market of Ruteng City, Manggarai Regency, East Nusa Teng- gara Province. The research method used is quantitative descriptive, namely analyzing market share and followed by multiple linear regression analysis as a tool to calculate: The research method used is quantitative descriptive, namely analyzing market share and followed by multiple linear regression analysis as a tool to calculate:1) classical assumption test consisting of normality test, multicollinarity test and heterokedasticity test and 2) hypothesis test with t-statistical test, F-statistical test and determination coefficient (R2). The results of the analysis show that pork is included in the type of essential goods, namely basic necessities or very important items in daily life. In general, the increase in income has no effect on the increase in the number of demands, as long as it is assumed for daily ne- eds. The results of the study concluded that the average demand was 594.5 Kg/month, with the highest quantity of meat demand at 1,882 Kg/month and the lowest at 187 Kg/month; the price of fresh pork, the price of other goods, and consumer preferences have a positive and significant influence on the demand for fresh pork in the traditional markets of Ruteng City, Manggarai Regency.